Combined Application of Sodium Fluorescein and Neuronavigation Techniques in the Resection of Brain Gliomas - Xue, Zhan; Kong, Lu; Hao, Shuyu; Wang, Yu; Jia, Guijun; Wu, Zhen; Jia, Wang; Zhang, Junting; Zhang, Liwei (Frontiers in Neurology, 2021)
Objectives: To explore the effectiveness and safety of combined application of sodium fluorescein and neuronavigation techniques in the resection of intracranial gliomas of different locations and ages. Methods: Fifty clinical cases of intracranial gliomas at department of Neurosurgery of Beijing Tiantan Hospital were collected from March 2014 to March 2019, which were divided into supratentorial group（24 cases）and brain-stem group (26 cases) by locations, adult group (28 cases) and pediatric group (22 cases) by ages. Fluorescein-guided surgery were performed (the adult group received 5 mg/kg of sodium fluorescein before opening the dura, while the child group received 2.5 mg/kg), during the resection. The tumor visualization was evaluated by the enhancement of the yellow-fluorescein and identified if the illumination was “satisfactory” for demarcating the tumor boundary, also the consistency between fluorescein and neuronavigation was analyzed. The KPS of all patients were recorded and assessed at admission, discharge and 6-month follow-up. Results: In the total 28 adult cases, 4 were unsatisfactory, while in the 22 child cases, 2 was unsatisfactory; for 7 cases, there were non-consistency between yellow fluorescein enhancement and neuronavigation, 6 from supratentorial group and 1 from brain-stem group. Statistical analysis showed no significant differences of satisfactory rate between adult and pediatric groups (P=0.575), whereas significant differences of consistency between supratentorial group and brain-stem group（P=0.031）. The mean KPS at admission were 70 to 100, which showed no significant differences from that of discharge (P=0.839), but KPS at 6-months follow-up significantly higher than that of admission（P=0.041）. Conclusions: The consistency between sodium fluorescein and neuronavigation system was higher in brain-stem group than supratentorial group; half dose of sodium fluorescein (2.5 mg/kg) is enough for pediatric patients. Combined utilization of sodium fluorescein and neuronavigation techniques may confer the patients of gliomas opportunities to get better clinical outcomes after the surgery.